2020
DOI: 10.22271/phyto.2020.v9.i2g.10885
|View full text |Cite
|
Sign up to set email alerts
|

Genetic variability, heritability and genetic advance for yield and its contributing traits in rice (Oryza sativa L.)

Abstract: The experiment on 125 genotypes (20 lines, 5 tester and 100 F1's) including a check viz., Pusa Basmati 6 of rice (Oryza sativa L.) was conducted to work out the genetic variability, heritability and genetic advance effects of their various attributes on grain yield. The mean squares due to treatments, parents and crosses were highly significant for all the fifteen characters indicated the presence of sufficient variability in the study materials. PCV was higher than the genotypic GCV for all the traits. High h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

20
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(28 citation statements)
references
References 7 publications
20
8
0
Order By: Relevance
“…The days to maturity and water consumption indicated higher GA under both treatments. A higher H 2 and high GA of days to maturity and water consumption exhibited that these traits were controlled by additive gene impacts, and similar findings for the agronomic traits of rice crops have also been reported by Chuchert et al [27], Sumanth et al [74] and Vange [75].…”
Section: Discussionsupporting
confidence: 83%
“…The days to maturity and water consumption indicated higher GA under both treatments. A higher H 2 and high GA of days to maturity and water consumption exhibited that these traits were controlled by additive gene impacts, and similar findings for the agronomic traits of rice crops have also been reported by Chuchert et al [27], Sumanth et al [74] and Vange [75].…”
Section: Discussionsupporting
confidence: 83%
“…In case of calyx length, similar high estimated in present investigation which was also reported earlier by Kumar et al (2013). The average fruit diameter was observed 6.28 cm, ranging from 3.16 to 11.88 cm with high estimates for all the genetic parameters and this high GCV and PCV was also reported by the Yadav et al (2016). High GCV (28.64%) and PCV (28.65%) coupled with high heritability (99.91%) and GAM (58.97%) was recorded for fruit length.…”
Section: Genetic Variability Heritability and Genetic Advancesupporting
confidence: 90%
“…Kumar et al (2013) and Lokesh et al (2013) in earlier also reported high GCV and PCV for fruit length in brinjal in their experiment. For fruit weight, high GCV (60.25%), PCV (60.25%),heritability (99.98%) and high GAM (124.10%) was observed which were in conformity with the earlier finding of Kumar et al (2012) and Yadav et al (2016). Whereas, high heritability coupled with GAM was reported by Muniappan et al (2010).…”
Section: Genetic Variability Heritability and Genetic Advancesupporting
confidence: 88%
See 1 more Smart Citation
“…Greater heritability marks the effectiveness of selection in improving a trait in the population (Acquaah, 2012). Mathematically, it is the ratio between genetic and phenotypic variance, which is generally categorized as high (above 60%), medium (30-60%), and low (below 30%) (Kumar et al, 2020).…”
Section: Introductionmentioning
confidence: 99%